2020
DOI: 10.1088/1755-1315/553/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dill Powder (Anethum graveolens) as a Dietary Supplement on Productive Performance, Mortality and Economic Figure in Broiler

Abstract: Background and Aim: Dill “Anethum graveolens” is considered to be an important herbal medicinal plant in the celery family “Apiaceae”. It is the only member of the genus “Anethum”. Dill seed’s health benefits include the potential to improve digestive health, as well as supplying insomnia, hiccups, respiratory disorders, nausea, dysentery, and cancer relief. This experiment was conducted to shed light the influences of dietary Dill leaves powder supplementation on growth performance, edible giblets and mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
0
1
Order By: Relevance
“…However, it has also been tested as growth promoter in fewer studies and has been found to improve FCR in broilers. In this study, however, we did not observe any better FCR by the use of anise seed instead we had observed highest dressing percentage for this quail group (El-Ashram S and Abdelhafez 2020; Hammod et al 2020;Mohamed et al 2020).…”
Section: Discussioncontrasting
confidence: 72%
“…However, it has also been tested as growth promoter in fewer studies and has been found to improve FCR in broilers. In this study, however, we did not observe any better FCR by the use of anise seed instead we had observed highest dressing percentage for this quail group (El-Ashram S and Abdelhafez 2020; Hammod et al 2020;Mohamed et al 2020).…”
Section: Discussioncontrasting
confidence: 72%
“…Controlling these foodborne organisms requires a broader understanding of how microbial pathogens enter and move through the food chain, as well as the conditions that promote or inhibit growth for each type of organism. It is generally known, that supplementation of poultry feed with antibiotic growth promoters (AGPs) improves performance of live-stock (91)(92)(93). The effect of AGPs on gut flora, results in improvement of digestion, better absorption of nutrients, and a more stable balance in the microbial population.…”
Section: Antibiotic Resistance and Associated Problemsmentioning
confidence: 99%